2015
DOI: 10.1371/journal.pone.0121071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Expression of Programmed Cell Death 1 Ligand 1 (PD-L1) in Malignant Pleural Mesothelioma (MPM)

Abstract: BackgroundThe increasing incidence and poor outcome associated with MPM requires finding effective treatment for this disease. PD1/PD-L1 pathway plays a central role in tumor immune evasion and appears to be predictive and prognostic marker. PD-L1 is expressed in many different human cancers but its role in MPM has yet to be established. The aim of this study is to evaluate the expression of PD-L1 in MPM.Methods119 MPM patients (p) from two institutions between November 2002 and February 2014 were reviewed. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(119 citation statements)
references
References 44 publications
10
98
4
1
Order By: Relevance
“…PD‐L1 appears to be expressed in a substantial proportion of human MPM 12, 24. Our IHC staining results also showed that 22.9% of human MPM had strong expression of PD‐L1, which indicate that some patients with MPM might benefit from anti‐PD‐1/PD‐L1 immunotherapy.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…PD‐L1 appears to be expressed in a substantial proportion of human MPM 12, 24. Our IHC staining results also showed that 22.9% of human MPM had strong expression of PD‐L1, which indicate that some patients with MPM might benefit from anti‐PD‐1/PD‐L1 immunotherapy.…”
Section: Discussionsupporting
confidence: 57%
“…Immunotherapy targeting the immune checkpoint programmed death‐1 (PD‐1)/PD‐ligand (L) 1 axis has been used to treat various cancers including non‐small‐cell lung cancer, melanoma, renal cell carcinoma and Hodgkin lymphoma 6, 7, 8, 9, 10. Recently, PD‐1/PD‐L1 inhibitors were also used to treat patients with advanced MPM, and several clinical trials are ongoing 11, 12. Tumour PD‐L1 expression has been used as a predictive biomarker for PD‐1/PD‐L1 inhibitors 6, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPM has a high variability of lymphocytic infiltration, but prolonged survival is associated with a higher presence of lymphoid cells (170). Additionally, PD-L1 expression is variable, is associated with populations of infiltrating T cells, and may be more associated with sarcomatoid histology and a worse prognosis (171)(172)(173)(174). Multiple clinical trials have sought to determine or are currently determining if MPM responds to immune mediated therapies ( Table 2).…”
Section: Immunotherapymentioning
confidence: 99%
“…Expression of programmed death-ligand 1 (PD-L1) on tumor cells and TILs has been described in literature. [6][7][8][9][10][11] However, only one series described PD-1 expression on tumor-infiltrating lymphocytes (TILs) 8 and nothing has been reported yet on TIM-3 and LAG-3 in human MPM tissue.…”
Section: Introductionmentioning
confidence: 99%